PERAN FINANCIAL CAPABILITY DAN FINANCIAL SECURITY DALAM MENINGKATKAN FINANCIAL SATISFACTION PEMILIK UMKM SEKTOR PARIWISATA DI MADURA - Mayada Pasha Umairoh; M. Boy Singgih Gitayuda; Purnamawati Purnamawati (J-MACC, 2024)
This article discusses the roles of financial capability and financial security in enhancing the financial satisfaction of Micro, Small, and Medium Enterprises (MSMEs) in the tourism sector in the Madura Region. Tourism in Madura holds significant economic potential, with MSMEs playing a crucial role in local economic development. Financial satisfaction serves as a subjective indicator of an individual's financial well-being. This study employs a descriptive approach using a quantitative method. The results of multiple linear regression analysis indicate that both financial capability and financial security exert a positive and significant influence on financial satisfaction. These findings substantiate the research hypothesis and underscore the importance of enhancing financial capability and financial security among tourism MSME owners in Madura. They offer valuable insights for MSME owners, local governments, educational institutions, and other stakeholders, facilitating the support of growth in the tourism sector MSMEs in Madura.